Animals in winter - Fisher, Ron, 1938- ([Washington, D.C.] : National Geographic Society, 1982)
Describes how animals face the rigors of winter by hibernating, migrating, storing food, or changing colors to blend with the winter landscape.
Keywords: Animals -- Wintering -- Juvenile literature; Animals -- Habits and behavior; Winter